Antimicrobial and antibiofilm activities of aqueous extracts of Cucurbita pepo L. - Silva, Ivanise Brito da; Sá, Rafaela Damasceno; Moura, Maiara Celine de; Coelho, Luana Cassandra Breitenbach Barroso; Randau, Karina Perrelli (Revista de Ciências Médicas e Biológicas, 2020)
Introduction: Cucurbita pepo L. is an herbaceous plant belonging to the family Cucurbitaceae. The species is popularly used in different countries for the treatment of diabetes and parasitic diseases. Objective: This study evaluated the antimicrobial and antibiofilm potential of aqueous extracts of leaves and seeds of C. pepo. Methodology: the extracts were tested in vitro against strains of Streptococcus pyogenes, Candida albicans and Candida krusei. The antimicrobial activity was performed by the microtiter method and the antibiofilm activity by the violet crystal method. Results: the results demonstrated that the extracts tested showed antibacterial and antibiofilm actions against S. pyogenes, but it was not possible to determine the minimum inhibitory concentration (MIC). The extracts inhibited the growth of C. albicans and C. krusei with MIC of 0.03 mg/mL. The antibiofilm activity of these species did not present either a dose dependence relationship or a synergistic effect when associated with the antifungal Fluconazole®. Conclusion: although there are indications of antimicrobial and inhibitory action in the formation of biofilm, additional studies are necessary to characterize the possible pharmacological effects of the analyzed specie